Method for synthesizing and purifying electronic grade phosphorane
GaN crystal growth is promoted by using high-temperature annealing process of silicon carbide ceramic substrates, ionic liquids and biological enzymes during phosphane preparation, and purifying the multi-stage adsorbent of modified metal organic frame materials, combined with laser irradiation, thermal cracking and multi-stage adsorbents for modified metal organic frame materials The technology solves the problems of low raw material purity and product purity in traditional methods, and realizes the preparation of high-purity electron-grade phosphane.
Patent Information
- Application Number
- CN202411535081.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional phosphane preparation methods are difficult to ensure high purity of raw materials, resulting in low purity of product and difficulty in removing impurities, making it impossible to obtain high-purity electron-grade phosphane.
Silicon carbide ceramic substrate is used to anneale and build a chemical vapor deposition reaction chamber, use ionic liquids and biological enzymes to promote the growth of gallium phosphide crystals, and generate phosphanes through laser irradiation and thermal cracking, and use modified metal organic frame materials and The multi-stage adsorbent is further purified.
The purity and quality of phosphonium alkyl is improved, the structural and chemical stability of the substrate is enhanced, the waste gas generation is reduced, the production efficiency is improved, and high purity electron-grade phosphonium alkyl is obtained.
Smart Images

Figure CN119461272A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phosphine synthesis, in particular to a method for synthesizing and purifying electronic-grade phosphine. Background Art
[0002] With the rapid development of electronic information technology, the semiconductor industry has an increasing demand for high-purity electronic-grade specialty gases. As an important electronic specialty gas, electronic-grade phosphine is widely used in semiconductor manufacturing, integrated circuits, optoelectronic devices and other fields. It is mainly used in the doping, epitaxial growth, etching and other processes of semiconductor materials. Its purity directly affects the performance and quality of electronic products. Under the current technical background, the traditional preparation method of phosphine has many problems and challenges. First, in terms of the selection and treatment of raw materials, traditional methods often cannot guarantee the high purity of raw materials. For example, when using ordinary purity phosphine and hydrogen as reaction raw materials, they may contain trace impurities, such as oxides, carbides, moisture, etc. These impurities will be introduced into the final product during the reaction process, reducing the purity of phosphine;
[0003] Traditional technology has certain technical defects. First, it is difficult to ensure that the substrate has high stability during the reaction, and it is impossible to effectively remove impurities to provide a good substrate for the growth of gallium phosphide crystals. Secondly, it is difficult to avoid side reactions when synthesizing and purifying phosphine to ensure the purity of the product. Furthermore, the existing technology cannot comprehensively and effectively remove impurities, and it is difficult to obtain high-purity electronic-grade phosphine to meet high-end needs. For this reason, we propose a method for synthesizing and purifying electronic-grade phosphine. Summary of the invention
[0004] The object of the present invention is to provide a method for synthesizing and purifying electronic grade phosphine.
[0005] To solve the problems raised in the above background technology, the present invention provides the following technical solution: a method for synthesizing and purifying electronic grade phosphine, the method specifically comprising the following steps:
[0006] Step 1: Select a silicon carbide ceramic substrate and perform high-temperature annealing treatment. Through annealing, metal oxides and carbide impurities that may exist in the substrate are removed, and the structural stability and chemical stability of the substrate in a high-temperature reaction environment are improved. Then, a chemical vapor deposition reaction chamber made of a corrosion-resistant alloy is built, and the annealed silicon carbide ceramic substrate is placed in the reaction chamber. Phosphine and hydrogen are selected as raw materials. In this process, an ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate is provided in the chemical vapor deposition reaction chamber. This ionic liquid has extremely low volatility, good thermal stability and designability, and can greatly reduce the generation of waste gas. During the growth of gallium phosphide crystals, the temperature of the reaction system is controlled to be 130°C-150°C. After a period of reaction, the temperature of the reaction system is controlled to gradually decrease. Subsequently, biological enzymes are added to the reaction chamber to promote the growth of gallium phosphide crystals. The biological enzymes can accelerate the reaction rate between phosphine and hydrogen, improve the selectivity of the reaction, and thus promote the directional growth of gallium phosphide crystals on the silicon carbide ceramic substrate.
[0007] Step 2: irradiate the grown gallium phosphide crystal with a continuous wave laser from a laser. During the irradiation process, the laser focus position and irradiation angle are precisely adjusted to ensure that the laser can act evenly on the surface of the gallium phosphide crystal. After a period of irradiation reaction, the gallium phosphide crystal is converted into a phosphine precursor, which is then thermally cracked to decompose the phosphine precursor in a high-temperature quartz tube to generate phosphine.
[0008] Step 3, preparing a new adsorption material, synthesizing and modifying a metal organic framework material (MOF), selecting an organic ligand and a metal ion to synthesize a metal organic framework material ZIF-8, and the modified ZIF-8 material has a strong adsorption capacity for trace impurities oxides and sulfides in phosphine, while the adsorption of phosphine is relatively weak;
[0009] Step 4: soak the activated carbon fiber in a dilute hydrochloric acid solution and then dry it as a primary adsorbent to perform preliminary adsorption on the macromolecular impurities in the crude phosphine. The phosphine gas after the preliminary adsorption is introduced into an adsorption column equipped with a zeolite molecular sieve for secondary adsorption to remove small and medium molecular impurities. The product after the secondary adsorption is then contacted with the prepared new MOF material for reaction, and the MOF material is used to further adsorb the residual trace impurities to improve the purity of the phosphine. Then, the phosphine is further purified by a distillation tower to obtain high-purity electronic-grade phosphine.
[0010] As a further solution of the present invention: in the step 1, the annealing temperature of the silicon carbide ceramic substrate is 1000° C.-1300° C., the duration is 5 h-8 h, the selected phosphine purity is 99.99%, the hydrogen purity is also 99.99%, and the flow ratio of hydrogen to phosphine is 5-7:1-3.
[0011] As a further scheme of the present invention: in the step 1, during the chemical vapor deposition reaction process of gallium phosphide crystal growth, the temperature of the ionic liquid is controlled to be 130°C-150°C 3h-4h before the reaction, and when the reaction proceeds to 3h-4h, the temperature of the reaction system is gradually reduced to 40°C-50°C, the added biological enzyme is glucose oxidase, and the biological enzyme catalyzed reaction temperature is 40°C-50°C.
[0012] As a further solution of the present invention: in the step 2, the laser is a gallium arsenide semiconductor laser, the laser wavelength is 450nm, the power is 200W, and the irradiation time is 30s-50s.
[0013] As a further solution of the present invention: in the step 2, the phosphine precursor is decomposed into phosphine in a high-temperature quartz tube by thermal cracking, and the specific operation is as follows: first, the quartz tube is placed in a heating furnace, starting from room temperature, and the heating rate of the heating furnace is controlled at 10°C / min-15°C / min, until the thermal cracking temperature is strictly controlled at 680°C-720°C, and inert gas argon is continuously introduced during the thermal cracking process, and the flow rate of argon is controlled at 10L / min-15L / min, and the duration is 3h-4h, to ensure that the phosphine precursor is completely decomposed into phosphine.
[0014] As a further scheme of the present invention: in the step three, the organic ligand is terephthalic acid, the metal ion is zinc ion, and the specific metal organic framework (MOF) modification method is: at a temperature of 80°C-100°C and a pressure of 1.5atm-1.7atm, ZIF-8 is immersed in an ethanol solution containing a 3-aminopropyltriethoxysilane functionalizing reagent with a concentration of 0.2mol / L-0.5mol / L, reacted for 8h-10h, taken out, and then washed with anhydrous ethanol for 3-5 times to remove unreacted reagents and impurities, and finally dried in a vacuum drying oven at 60°C-80°C for 12h-20h to obtain the modified ZIF-8 material.
[0015] As a further solution of the present invention: in step 4, the concentration of the dilute hydrochloric acid solution is 0.5 mol / L-0.8 mol / L, the immersion time is 4h-6h, and the surface area of the activated carbon fiber reaches 1500m 2 / g-1700m 2 / g.
[0016] As a further solution of the present invention: in the step 4, the pore size of the zeolite molecular sieve adsorption column is 0.2μm-0.5μm, and then the product after secondary adsorption is contacted with the prepared new MOF material for reaction, and the reaction temperature is controlled to be 50℃-70℃ and the pressure is 100Pa-140Pa.
[0017] As a further solution of the present invention: in the step 4, the distillation tower uses a stainless steel wire mesh filler, and performs distillation operation under vacuum conditions of a temperature of -90°C to -60°C and a pressure of 5Pa-7Pa, and the reflux ratio is controlled to be 3-5:1-3.
[0018] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:
[0019] 1. The present invention selects a silicon carbide ceramic substrate and performs a high-temperature annealing treatment to remove impurities such as metal oxides and carbides in the substrate, so that the atomic arrangement of the substrate is more regular and orderly, and the crystal structure is more complete, thereby having higher structural stability. At the same time, after removing the impurities, the interaction between the substrate and the reactants in a high-temperature reaction environment is more controllable, the chemical stability is enhanced, and a solid and reliable substrate is provided for the growth of gallium phosphide crystals. By adopting a new environmentally friendly solvent ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate, its extremely low volatility is utilized to reduce waste gas generation, which is more environmentally friendly. At the same time, by introducing glucose oxidase to carry out a catalytic reaction, the reaction rate between phosphine and hydrogen is accelerated, the selectivity of the reaction is improved, and the gallium phosphide crystal is promoted to grow efficiently and directional on the silicon carbide ceramic substrate, thereby improving product quality and production efficiency;
[0020] 2. The present invention uses a specific gallium arsenide semiconductor laser to irradiate gallium phosphide crystals, which can accurately control the action position and angle of the laser, ensuring that the laser acts evenly on the crystal surface. This method allows the gallium phosphide crystals to be efficiently converted into phosphine precursors, ensuring the reliability and consistency of the conversion process, and providing a good foundation for subsequent reactions. At the same time, a thermal cracking method is adopted, with the help of a suitable heating furnace and inert gas argon, to create a stable environment for the decomposition of the phosphine precursor. The thermal cracking process can effectively and completely decompose the precursor into phosphine, avoiding the occurrence of side reactions and ensuring the purity and quality of the product.
[0021] 3. The present invention uses activated carbon fibers that have undergone specific treatment as primary adsorbents to preliminarily adsorb macromolecular impurities in the synthetic product, and utilizes its large specific surface area and the characteristics after being soaked in a dilute hydrochloric acid solution to effectively remove macromolecular impurities in crude phosphine, laying the foundation for subsequent purification steps. Then, an adsorption column equipped with a zeolite molecular sieve with a specific pore size is used for secondary adsorption to remove small and medium molecular impurities, thereby further improving the purity of the phosphine. The phosphine that has undergone secondary adsorption is brought into contact with a specially synthesized and modified metal organic framework material, and under specific conditions, the material is used to further adsorb residual trace impurities, thereby greatly improving the purity of the product. Finally, in the distillation operation, a stainless steel wire mesh filler distillation tower is used to obtain high-purity electronic grade phosphine under the conditions of high vacuum, specific temperature and reflux ratio. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the method steps in an embodiment of the present invention;
[0023] Figure 2 It is a schematic diagram for comparing the performance of the embodiment and the comparative example in the embodiment of the present invention. DETAILED DESCRIPTION
[0024] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0025] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0026] Please see attached Figure 1 -Attached Figure 2 The present invention provides a method for synthesizing and purifying electronic grade phosphine, and the method for synthesizing and purifying the electronic grade phosphine specifically comprises the following steps:
[0027] Step 1: Select a silicon carbide ceramic substrate and perform high-temperature annealing treatment. Through annealing, metal oxides and carbide impurities that may exist in the substrate are removed, and the structural stability and chemical stability of the substrate in a high-temperature reaction environment are improved. Then, a chemical vapor deposition reaction chamber made of a corrosion-resistant alloy is built, and the annealed silicon carbide ceramic substrate is placed in the reaction chamber. Phosphine and hydrogen are selected as raw materials. In this process, an ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate is provided in the chemical vapor deposition reaction chamber. This ionic liquid has extremely low volatility, good thermal stability and designability, and can greatly reduce the generation of waste gas. During the growth of gallium phosphide crystals, the temperature of the reaction system is controlled to be 130°C-150°C. After a period of reaction, the temperature of the reaction system is controlled to gradually decrease. Subsequently, biological enzymes are added to the reaction chamber to promote the growth of gallium phosphide crystals. The biological enzymes can accelerate the reaction rate between phosphine and hydrogen, improve the selectivity of the reaction, and thus promote the directional growth of gallium phosphide crystals on the silicon carbide ceramic substrate.
[0028] Step 2: irradiate the grown gallium phosphide crystal with a continuous wave laser from a laser. During the irradiation process, the laser focus position and irradiation angle are precisely adjusted to ensure that the laser can act evenly on the surface of the gallium phosphide crystal. After a period of irradiation reaction, the gallium phosphide crystal is converted into a phosphine precursor, which is then thermally cracked to decompose the phosphine precursor in a high-temperature quartz tube to generate phosphine.
[0029] Step 3, preparing a new adsorption material, synthesizing and modifying a metal organic framework material (MOF), selecting an organic ligand and a metal ion to synthesize a metal organic framework material ZIF-8, and the modified ZIF-8 material has a strong adsorption capacity for trace impurities oxides and sulfides in phosphine, while the adsorption of phosphine is relatively weak;
[0030] Step 4: soak the activated carbon fiber in a dilute hydrochloric acid solution and then dry it as a primary adsorbent to perform preliminary adsorption on the macromolecular impurities in the crude phosphine. The phosphine gas after the preliminary adsorption is introduced into an adsorption column equipped with a zeolite molecular sieve for secondary adsorption to remove small and medium molecular impurities. The product after the secondary adsorption is then contacted with the prepared new MOF material for reaction, and the MOF material is used to further adsorb the residual trace impurities to improve the purity of the phosphine. Then, the phosphine is further purified by a distillation tower to obtain high-purity electronic-grade phosphine.
[0031] In one embodiment of the present invention: in step 1, the annealing temperature of the silicon carbide ceramic substrate is 1000° C.-1300° C., the duration is 5 h-8 h, the selected phosphine purity is 99.99%, the hydrogen purity is also 99.99%, and the flow ratio of hydrogen to phosphine is 5-7:1-3.
[0032] In one embodiment of the present invention: in step one, during the chemical vapor deposition reaction of gallium phosphide crystal growth, the temperature of the ionic liquid is controlled to be 130°C-150°C 3h-4h before the reaction, and when the reaction proceeds to 3h-4h, the temperature of the reaction system is gradually reduced to 40°C-50°C, the added biological enzyme is glucose oxidase, and the biological enzyme catalyzed reaction temperature is 40°C-50°C.
[0033] In one embodiment of the present invention: in step 2, the laser is a gallium arsenide semiconductor laser, the laser wavelength is 450nm, the power is 200W, and the irradiation time is 30s-50s.
[0034] In one embodiment of the present invention: in step 2, the phosphine precursor is decomposed into phosphine in a high temperature quartz tube by thermal cracking, and the specific operation is as follows: first, the quartz tube is placed in a heating furnace, starting from room temperature, and the heating rate of the heating furnace is controlled at 10°C / min-15°C / min, until the thermal cracking temperature is strictly controlled at 680°C-720°C, and inert gas argon is continuously introduced during the thermal cracking process, and the flow rate of argon is controlled at 10L / min-15L / min, and the duration is 3h-4h, to ensure that the phosphine precursor is completely decomposed into phosphine.
[0035] In one embodiment of the present invention: in step three, the organic ligand is terephthalic acid, the metal ion is a zinc ion, and the specific metal organic framework (MOF) modification method is: at a temperature of 80°C-100°C and a pressure of 1.5atm-1.7atm, ZIF-8 is immersed in an ethanol solution containing a 3-aminopropyltriethoxysilane functionalizing reagent with a concentration of 0.2mol / L-0.5mol / L, reacted for 8h-10h, taken out, and then washed with anhydrous ethanol for 3-5 times to remove unreacted reagents and impurities, and finally dried in a vacuum drying oven at 60°C-80°C for 12h-20h to obtain a modified ZIF-8 material.
[0036] In one embodiment of the present invention: in step 4, the concentration of the dilute hydrochloric acid solution is 0.5 mol / L-0.8 mol / L, the immersion time is 4h-6h, and the surface area of the activated carbon fiber reaches 1500m 2 / g-1700m 2 / g.
[0037] In one embodiment of the present invention: in step four, the pore size of the zeolite molecular sieve adsorption column is 0.2μm-0.5μm, and then the product after secondary adsorption is contacted with the prepared new MOF material for reaction, and the reaction temperature is controlled to be 50℃-70℃ and the pressure is controlled to be 100Pa-140Pa.
[0038] In one embodiment of the present invention: in step 4, the distillation tower uses a stainless steel wire mesh filler, and performs distillation operation under vacuum conditions of a temperature of -90°C to -60°C and a pressure of 5Pa-7Pa, and the reflux ratio is controlled to be 3-5:1-3.
[0039] Example 1, please refer to the attached Figure 1 -Attached Figure 2First, a silicon carbide ceramic substrate was selected and subjected to high-temperature annealing treatment at 1100°C for 5 hours to remove metal oxide and carbide impurities in the substrate and improve the structural stability and chemical stability of the substrate in a high-temperature reaction environment. Then, a chemical vapor deposition reaction chamber made of corrosion-resistant alloy was built, and the annealed silicon carbide ceramic substrate was placed in the reaction chamber. Phosphine with a purity of 99.99% and hydrogen with a purity of 99.99% were selected as raw materials, and the flow ratio of hydrogen to phosphine was 5:1. Ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate was set in the chemical vapor deposition reaction chamber, and the temperature of the reaction system was controlled to be 140°C 3.5 hours before the reaction. When the reaction proceeds to 3.5 hours, the temperature of the reaction system is gradually lowered to 45°C, and glucose oxidase is added to promote the growth of gallium phosphide crystals at 45°C. Then, a continuous wave laser with a wavelength of 450nm and a power of 200W is emitted by a gallium arsenide semiconductor laser to irradiate the grown gallium phosphide crystals. The focusing position and irradiation angle of the laser are precisely adjusted to ensure that the laser acts evenly on the surface of the gallium phosphide crystal. The irradiation time is 40s, so that the gallium phosphide crystals are converted into phosphine precursors, and then thermal cracking is performed to decompose the phosphine precursors in the high-temperature quartz tube to generate phosphine. The specific operation is to place the quartz tube in a heating furnace, starting from room temperature, at 12°C / m in was heated to 700°C at a heating rate, and an inert gas argon was continuously introduced at a flow rate of 12L / min during the thermal cracking process for 3.5h. Subsequently, a new adsorption material was prepared, and terephthalic acid was selected as an organic ligand and zinc ions to synthesize the metal organic framework material ZIF-8. At a temperature of 90°C and a pressure of 1.6atm, ZIF-8 was immersed in an ethanol solution containing a 3-aminopropyltriethoxysilane functionalizing agent with a concentration of 0.3mol / L. After reacting for 9h, it was taken out, washed with anhydrous ethanol 4 times, and dried in a vacuum drying oven at 70°C for 16h to obtain a modified ZIF-8 material. After that, the The activated carbon fiber dried after soaking in a dilute hydrochloric acid solution with a concentration of 0.6 mol / L for 5 hours was used as a primary adsorbent to preliminarily adsorb the macromolecular impurities in the crude phosphine. The phosphine gas after the preliminary adsorption was introduced into a zeolite molecular sieve adsorption column equipped with a pore size of 0.3 μm for secondary adsorption to remove small and medium molecular impurities. Finally, the product after the secondary adsorption was contacted with the prepared new MOF material at 60°C and a pressure of 120 Pa. The MOF material was used to further adsorb the residual trace impurities. The distillation tower was used to perform distillation operation under vacuum conditions of a temperature of -75°C and a pressure of 6 Pa. The reflux ratio was controlled to be 5:2 to obtain high-purity electronic grade phosphine.
[0040] Example 2, please refer to the attached Figure 1 -Attached Figure 2First, a silicon carbide ceramic substrate was selected and subjected to high-temperature annealing treatment at 1100°C for 5 hours to remove metal oxide and carbide impurities in the substrate and improve the structural stability and chemical stability of the substrate in a high-temperature reaction environment. Then, a chemical vapor deposition reaction chamber made of corrosion-resistant alloy was built, and the annealed silicon carbide ceramic substrate was placed in the reaction chamber. Phosphine with a purity of 99.99% and hydrogen with a purity of 99.99% were selected as raw materials, and the flow ratio of hydrogen to phosphine was 5:1. An ionic liquid sodium chloride solution was set in the chemical vapor deposition reaction chamber, and the temperature of the reaction system was controlled to be 140°C 3.5 hours before the reaction. When the reaction After 3.5 hours, the temperature of the reaction system was gradually reduced to 45°C and cooled naturally. Then, a continuous wave laser with a wavelength of 450nm and a power of 200W was emitted by a gallium arsenide semiconductor laser to irradiate the grown gallium phosphide crystal. The focusing position and irradiation angle of the laser were precisely adjusted to ensure that the laser acted evenly on the surface of the gallium phosphide crystal. The irradiation time was 40s, so that the gallium phosphide crystal was converted into a phosphine precursor, and then thermal cracking was performed to decompose the phosphine precursor in a high-temperature quartz tube to generate phosphine. The specific operation was to place the quartz tube in a heating furnace, starting from room temperature, and heating it to 700°C at a heating rate of 12°C / min. During the thermal cracking process, inert gas nitrogen was continuously introduced at a flow rate of 12 L / min for 3.5 h. Subsequently, a new adsorption material was prepared. Terephthalic acid was selected as an organic ligand and zinc ions were used to synthesize the metal organic framework material ZIF-8. At a temperature of 90 ° C and a pressure of 1.6 atm, ZIF-8 was immersed in an ethanol solution containing a 3-aminopropyltriethoxysilane functionalizing agent with a concentration of 0.3 mol / L. After reacting for 9 h, it was taken out and washed with anhydrous ethanol for 4 times. It was dried in a vacuum drying oven at 70 ° C for 16 h to obtain a modified ZIF-8 material. After that, it was treated with a concentration of 0.6 mol l / L dilute hydrochloric acid solution for 5 hours and then dried, activated carbon fiber was used as a primary adsorbent to preliminarily adsorb large molecular impurities in crude phosphine, and the phosphine gas after the preliminary adsorption was introduced into a zeolite molecular sieve adsorption column equipped with a pore size of 0.3μm for secondary adsorption to remove small and medium molecular impurities. Finally, the product after the secondary adsorption was contacted with the prepared new MOF material at 60℃ and a pressure of 120Pa, and the MOF material was used to further adsorb the residual trace impurities. The distillation tower was used to perform distillation operation under vacuum conditions of a temperature of -75℃ and a pressure of 6Pa, and the reflux ratio was controlled to be 5:2 to obtain high-purity electronic grade phosphine.
[0041] Example 3, please refer to the attached Figure 1 -Attached Figure 2First, a silicon carbide ceramic substrate was selected and subjected to high-temperature annealing treatment at 1300°C for 8 hours to remove metal oxide and carbide impurities in the substrate and improve the structural stability and chemical stability of the substrate in a high-temperature reaction environment. Then, a chemical vapor deposition reaction chamber made of corrosion-resistant alloy was built, and the annealed silicon carbide ceramic substrate was placed in the reaction chamber. Phosphine with a purity of 99.99% and hydrogen with a purity of 99.99% were selected as raw materials, and the flow ratio of hydrogen to phosphine was 5:3. Ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate was set in the chemical vapor deposition reaction chamber, and the temperature of the reaction system was controlled to be 140°C 3.0 hours before the reaction. When the reaction reaches 3.0, the temperature of the reaction system is gradually lowered to 45°C, and glucose oxidase is added to promote the growth of gallium phosphide crystals at 45°C. Then, a continuous wave laser with a wavelength of 450nm and a power of 200W is emitted by a gallium arsenide semiconductor laser to irradiate the grown gallium phosphide crystals. The focusing position and irradiation angle of the laser are precisely adjusted to ensure that the laser acts evenly on the surface of the gallium phosphide crystal. The irradiation time is 30s, so that the gallium phosphide crystals are converted into phosphine precursors, and then thermal cracking is performed to decompose the phosphine precursors in the high-temperature quartz tube to generate phosphine. The specific operation is to place the quartz tube in a heating furnace, starting from room temperature, at 15°C / m in was heated to 680°C at a heating rate, and an inert gas argon was continuously introduced at a flow rate of 10L / min during the thermal cracking process for 3.0h. Subsequently, a new adsorption material was prepared, and terephthalic acid was selected as an organic ligand and zinc ions to synthesize the metal organic framework material ZIF-8. At a temperature of 90°C and a pressure of 1.6atm, ZIF-8 was immersed in an ethanol solution containing a 3-aminopropyltriethoxysilane functionalizing agent with a concentration of 0.3mol / L. After reacting for 9h, it was taken out, washed with anhydrous ethanol 4 times, and dried in a vacuum drying oven at 70°C for 20h to obtain a modified ZIF-8 material. After that, the ZIF-8 was The activated carbon fiber dried after soaking in a dilute hydrochloric acid solution with a concentration of 0.5 mol / L for 4 hours was used as a primary adsorbent to preliminarily adsorb the macromolecular impurities in the crude phosphine. The phosphine gas after the preliminary adsorption was introduced into a zeolite molecular sieve adsorption column equipped with a pore size of 0.3 μm for secondary adsorption to remove small and medium molecular impurities. Finally, the product after the secondary adsorption was contacted with the prepared new MOF material at 60°C and a pressure of 120 Pa. The MOF material was used to further adsorb the residual trace impurities. The distillation tower was used to perform distillation operation under vacuum conditions of a temperature of -75°C and a pressure of 6 Pa. The reflux ratio was controlled to be 5:2 to obtain high-purity electronic grade phosphine.
[0042] Comparative Example 1
[0043] Using the electronic-grade phosphine provided in the patent document entitled “An apparatus and method for synthesizing and purifying electronic-grade phosphine” with application publication number “CN10492577A”;
[0044] Electronic grade phosphine The method for purifying electronic grade phosphine is:
[0045] Step S1: The reactor is sealed and evacuated, and then ultrapure water is added, and then 98% electronic grade sulfuric acid is added to mix with water to form 75L of a dilute sulfuric acid solution with a mass concentration of 30%, and 15kg of zinc phosphide powder with a purity of 99.8% is slowly added and stirred, and the reaction is carried out using the heat of solution of sulfuric acid. The reaction is carried out under vacuum and the reaction temperature is 65°C to obtain crude phosphine;
[0046] Step S2: the crude phosphine gas produced in step S1 passes through a condenser at a condensation temperature of -30°C to separate the liquid droplets in the gas;
[0047] Step S3: the crude phosphine gas obtained in step S2 is passed through a drying tower to remove moisture entrained in the gas;
[0048] Step S4: passing the crude phosphine obtained in step S3 into a transfer container, and then placing the transfer container into a first liquid nitrogen cold trap for freezing and collection to solidify the phosphine;
[0049] Step S5: After the zinc phosphide powder in the reactor has reacted completely, the valve at the entrance of the transfer container is closed, the transfer container in step S4 is first evacuated by a vacuum pump to remove the non-condensable gas, and then the phosphine therein is heated to 30° C. to generate phosphine gas. At the same time, an oxidant (2% concentration of potassium permanganate solution) is added to the reactor to fully oxidize the phosphine dissolved in the sulfuric acid solution to ensure the safety of the treatment of reaction by-products;
[0050] Step S6: the phosphine gas obtained in step S5 is introduced into the first distillation tower, and the phosphine is introduced into the middle position of the first distillation tower; adopting normal temperature distillation, controlling the distillation temperature between 20°C, controlling the distillation pressure at 8 bar, and distilling the phosphine to remove light component impurities; the top of the first distillation tower is provided with a first top condenser, the condensation temperature is -10°C, a part of the phosphine liquid condensed by the first top condenser is refluxed to the first distillation tower, and the other part of the phosphine liquid enters the second distillation tower, the uncondensed tail gas of the top condenser is discharged into the waste gas treatment system, the bottom of the tower is provided with a first bottom reboiler, and the first bottom reboiler is heated to 30°C by using a heat medium (electric heating blanket), and the phosphine generated by heating enters the first distillation tower for distillation;
[0051] Step S7: the phosphine liquid in step S6 is introduced into the middle position of the second distillation tower, and the phosphine is distilled to remove heavy impurities by adopting normal temperature distillation, controlling the distillation temperature between 22° C. and the distillation pressure at 7 bar; the second distillation tower is provided with a second top condenser at a condensation temperature of -10° C., a part of the phosphine liquid condensed by the second top condenser is refluxed to the second distillation tower, and another part of the phosphine gas at the top of the tower enters the chemical adsorption column; a second bottom reboiler is provided at the bottom of the tower, and the second bottom reboiler is heated to 30° C. by using a heat medium (electric heating blanket), and the phosphine generated by heating enters the second distillation tower for distillation;
[0052] Step S8: passing the product gas obtained in step S7 into a chemical adsorption column containing alkaline substance sodium hydroxide to remove impurities containing sulfide; and then passing it into a molecular sieve adsorption column to remove impurities containing water, oxygen, carbon dioxide, etc.;
[0053] Step S9: passing the phosphine gas obtained in step S8 into a collection container, placing the collection container in a second liquid nitrogen cold trap to solidify the phosphine, and then vacuuming again to remove the non-condensable gas, and finally obtaining a high-purity phosphine product.
[0054] Experimental design
[0055] Silicon carbide ceramic substrate, phosphine with a purity of 99.99%, hydrogen with a purity of 99.99%, ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate, glucose oxidase, gallium arsenide semiconductor laser, quartz tube, heating furnace, inert gas argon, terephthalic acid, zinc ion, 3-aminopropyltriethoxysilane functionalization reagent, ethanol, 0.6 mol / L dilute hydrochloric acid solution, activated carbon fiber, zeolite molecular sieve, metal organic framework material ZIF-8, etc.
[0056] The materials and equipment prepared according to the method of Comparative Example 1 include ultrapure water, 98% electronic grade sulfuric acid, zinc phosphide powder, an oxidant (2% potassium permanganate solution), a condenser, a drying tower, a transfer container, a first liquid nitrogen cold trap, a first distillation tower, a first tower top condenser, a first tower bottom reboiler, a second distillation tower, a second tower top condenser, a second tower bottom reboiler, a chemical adsorption column, a molecular sieve adsorption column, a collecting container, a second liquid nitrogen cold trap, etc.;
[0057] Experimental steps: The synthesis and purification of electronic grade phosphine were carried out by using the methods of Example 1, Example 2, Example 3 and Comparative Example 1 respectively, and the experiments were repeated three times for each;
[0058] The electronic grade phosphine obtained in each experiment is tested for the following indicators:
[0059] Purity detection: The purity of phosphine is detected by gas chromatography. The sample is injected into the gas chromatograph, and the purity of the sample is calculated by comparing the peak area with the standard of known purity. The calculation formula is: Purity = peak area of phosphine in the sample / total peak area × 100%;
[0060] Impurity content detection: detection includes oxides, sulfides, moisture, oxygen, carbon dioxide and other impurities. Specific detection instruments, such as infrared spectrometer, trace moisture meter, etc., are used to detect various impurities. The impurity content is expressed in ppm, that is, the number of impurities per million samples. The calculation formula is: impurity content = mass of impurities / total mass of samples × 1000000;
[0061] Structural stability test: the obtained phosphine is placed in a specific constant temperature and constant pressure container, placed at a certain temperature (50° C.) and pressure (1 atm) for 48 hours, and then the density change of the phosphine before and after the placement is measured, structural stability parameter = (density before placement - density after placement) / density before placement × 100%, the smaller the value, the higher the structural stability. When the value is less than 0.1%, it is evaluated as high stability, 0.1%-0.5% is evaluated as relatively high stability, and greater than 0.5% is evaluated as general stability;
[0062] Chemical stability test: Phosphine was contacted with an acidic solution (0.1 mol / L hydrochloric acid solution) and an alkaline solution (0.1 mol / L sodium hydroxide solution) of a certain concentration, respectively, and placed at a specific temperature (25°C) for 24 hours, and then the purity change of the phosphine was detected. Chemical stability parameter = (purity before contact - purity after contact) / purity before contact × 100%. The smaller the value, the higher the chemical stability. When the value is less than 0.2%, it is evaluated as high stability, 0.2%-0.5% is evaluated as relatively high stability, and greater than 0.5% is evaluated as general stability.
[0063] Production efficiency test: record the time required for each method from the beginning to obtain high-purity electronic-grade phosphine. The production efficiency is measured in hours. The time from the beginning of raw material preparation to the final acquisition of high-purity electronic-grade phosphine is the production efficiency.
[0064] As attached Figure 2 As shown, by comparing the electronic grade phosphine synthesis and purification methods of Example 1, Example 2, Example 3 and Comparative Example 1, the results show that Example 1 performs well in purity, impurity content, structural stability, chemical stability and production efficiency, and effectively improves the quality and production efficiency of phosphine. Although Examples 2 and 3 are better than Comparative Example 1 in some indicators, there is still a gap compared with Example 1, which fully proves the superiority and innovation of the method of Example 1.
[0065] At the same time, the present application uses specific words to describe the embodiments of the present application, such as "one embodiment", "an embodiment", and / or "some embodiments" to refer to a certain feature, structure or characteristic related to at least one embodiment of the present application. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or more in different places in this specification does not necessarily refer to the same embodiment. In addition, certain features, structures or characteristics in one or more embodiments of the present application may be appropriately combined.
[0066] Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any changes, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for synthesizing and purifying electronic grade phosphine, characterized in that: The synthesis and purification method specifically comprises the following steps: Step 1: Select a silicon carbide ceramic substrate, perform high-temperature annealing treatment, and then build a chemical vapor deposition reaction chamber, place the annealed silicon carbide ceramic substrate in the reaction chamber, select phosphine and hydrogen as raw materials, and in this process, the chemical vapor deposition reaction chamber is provided with an ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate, and the temperature of the reaction system is controlled to be 130°C-150°C during the growth of gallium phosphide crystals. After a period of reaction, the temperature of the reaction system is controlled to gradually decrease, and then biological enzymes are added to the reaction chamber to promote the growth of gallium phosphide crystals; Step 2: irradiating the grown gallium phosphide crystal with a continuous wave laser from a laser, and after a period of irradiation reaction, the gallium phosphide crystal is converted into a phosphine precursor, and then thermal cracking is performed to decompose the phosphine precursor in a high-temperature quartz tube to generate phosphine; Step 3: Prepare a new adsorption material, synthesize and modify the metal organic framework material (MOF), select organic ligands and metal ions to synthesize the metal organic framework material ZIF-8; Step 4: soak the activated carbon fiber in a dilute hydrochloric acid solution and then dry it as a primary adsorbent, then use the primary adsorbent to preliminarily adsorb the macromolecular impurities in the crude phosphine, introduce the phosphine gas after the preliminary adsorption into an adsorption column equipped with a zeolite molecular sieve for secondary adsorption to remove small and medium molecular impurities, and then contact the product after the secondary adsorption with the prepared new MOF material for reaction. After the reaction is completed, use a distillation tower to further purify the phosphine to obtain high-purity electronic grade phosphine.
2. The method for synthesizing and purifying electronic-grade phosphine according to claim 1, characterized in that: In the step 1, the annealing temperature of the silicon carbide ceramic substrate is 1000° C.-1300° C., the duration is 5 h-8 h, the purity of the selected phosphine is 99.99%, the purity of the hydrogen is also 99.99%, and the flow ratio of hydrogen to phosphine is 5-7:1-3.
3. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In the step 1, during the chemical vapor deposition reaction process of gallium phosphide crystal growth, the temperature of the ionic liquid is controlled to be 130°C-150°C 3h-4h before the reaction, and when the reaction proceeds to 3h-4h, the temperature of the reaction system is gradually reduced to 40°C-50°C, the added biological enzyme is glucose oxidase, and the biological enzyme catalyzed reaction temperature is 40°C-50°C.
4. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In the step 2, the laser is a gallium arsenide semiconductor laser, the laser wavelength is 450nm, the power is 200W, and the irradiation time is 30s-50s.
5. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In the step 2, the phosphine precursor is decomposed into phosphine in a high-temperature quartz tube by thermal cracking. The specific operation is as follows: first, the quartz tube is placed in a heating furnace, starting from room temperature, and the heating rate of the heating furnace is controlled at 10°C / min-15°C / min, until the thermal cracking temperature is strictly controlled at 680°C-720°C, and inert gas argon is continuously introduced during the thermal cracking process, and the flow rate of argon is controlled at 10L / min-15L / min, and the duration is 3h-4h, to ensure that the phosphine precursor is completely decomposed into phosphine.
6. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In the step three, the organic ligand is terephthalic acid, the metal ion is zinc ion, and the specific metal organic framework (MOF) modification method is: at a temperature of 80°C-100°C and a pressure of 1.5atm-1.7atm, ZIF-8 is immersed in an ethanol solution containing a 3-aminopropyltriethoxysilane functionalizing reagent with a concentration of 0.2mol / L-0.5mol / L, reacted for 8h-10h, taken out, and then washed with anhydrous ethanol for 3-5 times to remove unreacted reagents and impurities, and finally dried in a vacuum drying oven at 60°C-80°C for 12h-20h to obtain a modified ZIF-8 material.
7. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In step 4, the concentration of the dilute hydrochloric acid solution is 0.5 mol / L-0.8 mol / L, and the immersion time is 4 h-6 h, so that the surface area of the activated carbon fiber reaches 1500 m 2 / g-1700m 2 / g.
8. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In the step 4, the pore size of the zeolite molecular sieve adsorption column is 0.2 μm-0.5 μm, and then the product after the secondary adsorption is contacted with the prepared new MOF material for reaction, and the reaction temperature is controlled to be 50° C.-70° C. and the pressure is controlled to be 100 Pa-140 Pa.
9. The method for synthesizing and purifying electronic grade phosphine according to claim 1, characterized in that: In the step 4, the distillation tower uses a stainless steel wire mesh filler, and performs distillation operation under vacuum conditions of a temperature of -90°C to -60°C and a pressure of 5Pa-7Pa, and the reflux ratio is controlled to be 3-5:1-3.
Citation Information
Cited By
Preparation method of phosphorane
CN120463164A